New methods of varicose veins treatment - Kamil Bałabuszek (Journal of Education, Health and Sport, 2018)
Chronic venous disease may affect even 60% of the population. Manifestation of this condition may vary from no symptoms to an active venous ulcer. The treatment of this disease may improve patient’s quality of life. A large number of new studies have been carried out since the guidelines publication of the Society for Vascular Surgery, American Venous Forum and European Society for Vascular Surgery considering chronic venous disease treatment. There is also available a 2 year follow-up of the study described in the guidelines. New non- thermal techniques like Mechanochemical ablation (MOCA) and Cyanoacrylate closure (CAC) are very effective, less painful and safe. The use of endovenous non- thermal ablation techniques doesn’t require tumescent anaesthesia which works as a heat sink protecting surrounding tissues from damage in thermal techniques. This eliminates the risk of bleeding and pain associated with multiple needle injections along the vein section to be treated. New studies show that MOCA and CAC techniques have high closure rates directly after the procedure and in the follow-up periods.